Crystal size and crystalline volume fraction effects on the Erbium emission of nc-Si:Er grown by r.f. sputtering - Cerqueira, M. F. (2010)
Erbium-doped low-dimensional Si films with different microstructures were grown by reactive magnetron sputtering on glass substrates by varying the deposition parameters. Their structure and chemical composition were studied by micro-Raman and Rutherford backscattering spectrometry, respectively. In this contribution the Erbium emission is studied as a function of nanocrystalline fraction and average crystal sizes and also as a function of the matrix chemical composition. We discuss the temperature dependence of the Er3+ emission as well as the possible explanations of the low Er active fraction.